A FAUX TUMOUR OF THE CANCER - Dr. Kosuri Akhila; Dr.Suresh Kanna. S; Dr. Mathisha Ebby Perin; Dr. Keerthana; Radha Samyuktha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Browns tumour is a rare tumour like lesion of the bone, which is considered as an end stage lesion of abnormal bone metabolism caused by persistently high parathyroid hormone levels. These are highly vascular osteopathic lesions. In hyperparathyroidism patients instead of neoplasticism it depicts a reparable cellular process. Either these tumours can be aggressive or destructive. It can be seen in any part of the skeleton. Sometimes it can be seen multiple bones and misdiagnosed as metastatic tumour